2017
DOI: 10.3945/jn.116.243261
|View full text |Cite
|
Sign up to set email alerts
|

Rosa Mosqueta Oil Prevents Oxidative Stress and Inflammation through the Upregulation of PPAR-α and NRF2 in C57BL/6J Mice Fed a High-Fat Diet

Abstract: Rosa mosqueta (RM) oil is characterized by high concentrations of antioxidants and α-linolenic acid (ALA; 18:3n-3). We have previously demonstrated in male C57BL/6J mice that RM decreases hepatic steatosis, a condition strongly associated with oxidative stress and inflammation. We studied the molecular mechanisms that underlie the role of RM in preventing high-fat diet (HFD)-induced oxidative stress and inflammation. Male C57BL/6J mice aged 28 d and weighing 12-14 g were divided into the following groups and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Furthermore, there was an increased lipid peroxidation in the liver in response to steatosis and excess substrate (lipids) for peroxidation, and tissue oxidative damage was evidenced by histopathological alterations in the liver and increases in plasmatic liver health-related biomarkers, AST and ALT. The results described herein corroborate previous studies such as those carried out by Sarna et al [49], González-Mañán et al [50], and Venezuela et al [22], who indicated impaired glucose metabolism, increased hepatic liver injury enzyme markers, lipid peroxidation, and reduction in antioxidant enzyme activities in high-fat fed animals.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, there was an increased lipid peroxidation in the liver in response to steatosis and excess substrate (lipids) for peroxidation, and tissue oxidative damage was evidenced by histopathological alterations in the liver and increases in plasmatic liver health-related biomarkers, AST and ALT. The results described herein corroborate previous studies such as those carried out by Sarna et al [49], González-Mañán et al [50], and Venezuela et al [22], who indicated impaired glucose metabolism, increased hepatic liver injury enzyme markers, lipid peroxidation, and reduction in antioxidant enzyme activities in high-fat fed animals.…”
Section: Discussionsupporting
confidence: 92%
“…The binding of oestrogen to membrane ER directly phosphorylates PPAR- α and increases the intracellular concentration of DHA, which indirectly activates PPAR- α via elevated Ca phospholipase A 2 ( 7 ) . The present study and previous studies ( 21 , 39 ) consistently showed that low-LA diets increase PPAR- α expression. Therefore, the combination of oestrogen and a low-LA diet have an added effect on PPAR- α expression.…”
Section: Discussionsupporting
confidence: 91%
“…Keap1 has been identified as a cytosolic binding protein for Nrf2, which is associated with the Kelch domain of Keap1. Keap1 is sequestered in association with the actin cytoskeleton under normal physiological conditions, which in turn allows for proteasome degradation of Nrf2 [ 35 ]. In the present study, the Nrf2 protein expression level was increased and the Keap1 protein expression level was decreased, which indicated that the Nrf2 pathway was activated by dietary resveratrol supplementation.…”
Section: Discussionmentioning
confidence: 99%